2022
DOI: 10.1111/1742-6723.13943
|View full text |Cite
|
Sign up to set email alerts
|

‘I was prepared to become infected as a frontline medical staff’: A survey of Australian emergency department staff experiences during COVID‐19

Abstract: Objective To identify challenges faced by Australian hospital healthcare staff during the COVID‐19 pandemic. Methods We conducted an online survey (30 June–15 August 2020) of healthcare staff from Australian emergency and infectious disease departments. Participants were contacted via professional organisations and asked about preparedness, personal protective equipment (PPE), information flow, patient care, infection concerns, workload and mental health. We calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…These increases were related to healthcare workers undertaking activities that they do not usually do (Bellanti et al, 2021; Fernández‐Castillo et al, 2021; Gomez et al, 2020; Koh et al, 2005; Zhang, Xiang, & Alejok, 2021) or increasing work content (Jiang et al, 2022; Shoja et al, 2020), including changes to documentation (Fournier et al, 2022; Gomez et al, 2020), demand (Gomez et al, 2020; Tang et al, 2021; Villar et al, 2021; Wanninayake et al, 2022; Zamanzadeh et al, 2021; Zhan et al, 2020), skills required (Jiang et al, 2022; Liang et al, 2021; Tang et al, 2021; Wanninayake et al, 2022) and patient characteristics (Bruyneel, Gallani, et al, 2021; Felice et al, 2020), including isolation (Fernández‐Castillo et al, 2021). An increase in working overtime hours or more hours per day/week (Bellanti et al, 2021; Daneshvar et al, 2022; Duru, 2021; Evcili & Demirel, 2022; Fournier et al, 2022; Gao et al, 2020; Koh et al, 2005; Malinowska‐Lipień et al, 2021; Matsuo et al, 2021; Niu et al, 2022; Ozkan & Unlu, 2021; Ren et al, 2022; Said & El‐Shafei, 2021; Sethi et al, 2020; Zhan et al, 2020; Zhang, Xiang, & Alejok, 2021), an increase in healthcare provider‐patient ratios (Bergman et al, 2021; Bruyneel, Smith, et al, 2021; Cheong et al, 2022; Evcili & Demirel, 2022; García‐Hedrera et al, 2021; González‐Gil et al, 2021; Hoogendoorn et al, 2021; Ren et al, 2022; Scott et al, 2022), staffing shortages (Brophy et al, 2021; Evcili & Demirel, 2022; Fournier et al, 2022; González‐Gil et al,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These increases were related to healthcare workers undertaking activities that they do not usually do (Bellanti et al, 2021; Fernández‐Castillo et al, 2021; Gomez et al, 2020; Koh et al, 2005; Zhang, Xiang, & Alejok, 2021) or increasing work content (Jiang et al, 2022; Shoja et al, 2020), including changes to documentation (Fournier et al, 2022; Gomez et al, 2020), demand (Gomez et al, 2020; Tang et al, 2021; Villar et al, 2021; Wanninayake et al, 2022; Zamanzadeh et al, 2021; Zhan et al, 2020), skills required (Jiang et al, 2022; Liang et al, 2021; Tang et al, 2021; Wanninayake et al, 2022) and patient characteristics (Bruyneel, Gallani, et al, 2021; Felice et al, 2020), including isolation (Fernández‐Castillo et al, 2021). An increase in working overtime hours or more hours per day/week (Bellanti et al, 2021; Daneshvar et al, 2022; Duru, 2021; Evcili & Demirel, 2022; Fournier et al, 2022; Gao et al, 2020; Koh et al, 2005; Malinowska‐Lipień et al, 2021; Matsuo et al, 2021; Niu et al, 2022; Ozkan & Unlu, 2021; Ren et al, 2022; Said & El‐Shafei, 2021; Sethi et al, 2020; Zhan et al, 2020; Zhang, Xiang, & Alejok, 2021), an increase in healthcare provider‐patient ratios (Bergman et al, 2021; Bruyneel, Smith, et al, 2021; Cheong et al, 2022; Evcili & Demirel, 2022; García‐Hedrera et al, 2021; González‐Gil et al, 2021; Hoogendoorn et al, 2021; Ren et al, 2022; Scott et al, 2022), staffing shortages (Brophy et al, 2021; Evcili & Demirel, 2022; Fournier et al, 2022; González‐Gil et al,…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Bruyneel, Gallani, et al (2021) and Hoogendoorn et al (2021) identified that nursing activity scores were higher among the COVID‐19 patients as they required more time, which increased nursing workloads. However, some of the participants in these studies also reported a reduction in their workloads (Akova et al, 2022; Arslan et al, 2021; Butera et al, 2021; Felice et al, 2020; García‐Hedrera et al, 2021; Li et al, 2021; Matsuo et al, 2021; Nahidi et al, 2022; Scott et al, 2022). For example, Butera et al (2021) identified that 2.3% of nurses in the ICU and 37% in the emergency department reported a decrease in workload.…”
Section: Resultsmentioning
confidence: 99%
“…Managing the pandemic is a particular challenge for primary care. 1,2 As many general practitioners (GP) had no previous experience of dealing with such a pandemic, it caught most of them unprepared and completely changed their work situation. 3 For GPs, the psychological stress of responding to the pandemic was partly related to their role as the first point of contact for infected patients.…”
Section: Introductionmentioning
confidence: 99%